Foraging ecology of short-tailed shearwaters near the Pribilof Islands, Bering Sea - Hunt, GL; Coyle, KO; Hoffman, S; Decker, MB; Flint, EN (Marine Ecology Progress Series, 1996)
We studied short-tailed shearwaters Puffinus tenuirostris foraging near the Pribilof Islands, Alaska, USA, during the summers of 1987, 1988, and 1989. Their foods were almost exclusively the euphausiid Thysanoessa raschii, which they obtained both from near-surface swarms and from epibenthic layers. Near-surface mating swarms of euphausiids occurred in areas of elevated phytoplankton standing stocks near inshore tidal fronts. Many of these euphausiids had attached spermatophores. Shearwaters also obtained euphausiids over shallow reefs and inshore of the fronts where euphausiids were trapped in water shallower than 40 m by irregularities in bottom topography ('bathymetric traps'). We hypothesize that the largely inshore distribution of shearwaters in the southeastern Bering Sea described by previous workers is the result of attraction of shearwaters to frontal areas where euphausiids may forage on phytoplankton stocks throughout the summer. These areas, when shallower than 40 m, would also permit shearwaters to access epibenthic aggregations of euphausiids during daylight, when euphausiids not engaged in mating swarms usually migrate to depth.